2007
DOI: 10.1159/000099300
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Low to Moderate Myopia on Retinal Nerve Fiber Layer as Assessed by Scanning Laser Polarimetry with Variable Corneal Compensator

Abstract: Purpose: To evaluate the influence of different degrees of myopia on retinal nerve fiber layer (RNFL) as measured by scanning laser polarimetry (SLP) with variable corneal compensator (VCC) in healthy eyes. Methods: One hundred and seventy-four healthy age-matched subjects with low to high myopic and emmetropic eyes underwent RNFL measurement by means of GDxVCC. The GDx parameters included in the analysis were: Temporal-superior-nasal-inferior thickness (TSNIT) average, Superior average, Inferior average, TSNI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Recently, Vetrugno et al found no correlation between RNFL thickness and SE in 86 myopic eyes (mean refractive error −3.9±1.5 D, range−2.00–−8.25 D) using GDx VCC. Of note, data on axial length and TSS were not mentioned in the study 9. It has been demonstrated that atypical retardation patterns (ARPs) are associated with myopia and can cause inaccurate measurement 17.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recently, Vetrugno et al found no correlation between RNFL thickness and SE in 86 myopic eyes (mean refractive error −3.9±1.5 D, range−2.00–−8.25 D) using GDx VCC. Of note, data on axial length and TSS were not mentioned in the study 9. It has been demonstrated that atypical retardation patterns (ARPs) are associated with myopia and can cause inaccurate measurement 17.…”
Section: Discussionmentioning
confidence: 97%
“…Using OCT-1, Hoh et al did not find any significant association between RNFL thickness and axial length/SE,5 while recent studies based on OCT 3 (StratusOCT; Carl Zeiss Meditec Inc, Dublin, CA, USA; the time domain technology) have reported a negative relationship between RNFL thickness and axial length 6–8. However, no such evident correlation between RNFL and myopia was found in a recent study based on SLP with variable corneal compensator (GDx VCC) 9. Thus, the association between RNFL thickness and myopia is controversial.…”
Section: Introductionmentioning
confidence: 95%
“…19 In addition, low-to-high myopia is not related to clinically relevant variations of the parameters measured with SLP, as assessed with the GDx VCC device. 20 Several studies have evaluated the diagnostic capability of GDx VCC in glaucoma detection, especially at its early stages. [4][5][6][7] Weinreb et al 4 showed that the parameter with the largest AROC (0.83) for discriminating 54 glaucomatous eyes (average MD: 6.49 dB) from 40 healthy eyes was the average RNFL thickness within the superior quadrant.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study comparing between myopic and emmetropic eyes, Vetrugno et al found thicker superior and inferior RNFL and a thicker temporal RNFL, also by using a scanning laser polarimetry. 40 These findings showed that optic nerve parameters vary greatly with the methods used and the degrees of myopia.…”
Section: Association Of Hrt Parameters With Gender Age and Refractivmentioning
confidence: 94%